Modulation of interleukin-1β-induced inflammatory responses by a synthetic cationic innate defence regulator peptide, IDR-1002, in synovial fibroblasts - Turner-Brannen, Emily (BioMed Central, 2011)
INTRODUCTION: Innate defence regulator (IDR) peptides are synthetic cationic peptides, variants of naturally occurring innate immune effector molecules known as host defence peptides. IDR peptides were recently demonstrated to limit infection-associated inflammation selectively without compromising host innate immune functions. This study examined the impact of a 12-amino acid IDR peptide, IDR-1002, in pro-inflammatory cytokine interleukin (IL)-1β-induced responses in synovial fibroblasts, a critical cell type in the pathogenesis of inflammatory arthritis. METHODS: Human fibroblast-like synoviocytes (FLS) were stimulated with IL-1β in the presence and absence of IDR-1002. Production of enzyme matrix metalloproteinase-3 (MMP-3) and IL-1-receptor antagonist (IL-1RA) was monitored by enzyme-linked immunosorbent assay (ELISA), and various chemokines were evaluated by using multiplex cytometric bead array. Transcriptional responses were analyzed by quantitative real-time PCR. The impact on IL-1β-induced proteome was investigated by quantitative proteomics by using isobaric tags. IL-1β-induced pathways altered by IDR-1002 implicated by the proteomics analyses were further investigated by using various immunochemical assays. Cellular uptake of the peptide was monitored by using a biotinylated IDR-1002 peptide followed by microscopy probing with streptavidin-Alexa Fluor. RESULTS: This study demonstrated that IDR-1002 suppressed the production of IL-1β-induced MMP-3 and monocyte chemotactic protein-1 (MCP-1); in contrast, IDR-1002 enhanced the production of IL-1RA, without neutralizing all chemokine responses. IDR-1002 altered the IL-1β-induced proteome primarily by altering the expression of members of nuclear factor kappa-B (NF-κB) and c-Jun N-terminal kinase (JNK) pathways. The proteomics data also suggested that IDR-1002 was altering the transcription factor HNF-4α-mediated responses, known to be critical in metabolic regulation. With various immunochemical assays, it was further demonstrated that IL-1β-induced NF-κB, JNK, and p38 mitogen-activated protein kinase (MAPK) activations were significantly suppressed by IDR-1002. CONCLUSIONS: This study demonstrates the ability of an innate immune-modulatory IDR-peptide to influence the IL-1β-induced regulatory pathways and selectively to suppress inflammatory responses in synovial fibroblasts. The results of this study provide a rationale for examining the use of IDR-peptides as potential therapeutic candidates for chronic inflammatory diseases such as inflammatory arthritis.